Electromagnetic heating and motion mechanism for contact welded pipes based on a node sequential number method. (5th June 2018) - Han, Yi; Xiao, Yao; Yu, En-Lin; Wang, Li-Min
Highlights: Expounds a calculation method for heating of relatively complex workpieces. The axial temperature field in pipe blank exhibits an asymmetric sandglass. Temperature difference in the wall thickness direction can be decreased. Abstract: In recent years, welded pipes have been used widely in deepwater and polar regions. The electromagnetic heating for contact welded pipes is a key process for producing high-quality piping. The understanding of an accurate three-dimension profile of welding heat sources and evolution have been a subject for decades. In this paper, based on the features of mobile electromagnetic heating, a node sequential number method is proposed to equivalently characterize the motion of the loaded pipe blank. The axial temperature of the pipe blank is found to exhibit an asymmetric-sandglass typed distribution. This can be interpreted by the observation that the inlet side of the welded V point depends strongly on the thermal effect of the eddy current, while the other side is mainly affected by the motion of the pipe blank. The study verifies a calculation method for the moving electromagnetic heating imposed by a node sequential number method and, also, is expected to assist in promoting the intensive applications of the electromagnetic heating in the future.